Prevalence of benign pathology after partial nephrectomy for suspected renal tumor: A systematic review and meta-analysis. (December 2020) - Kim, Jae Heon; Shim, Sung Ryul; Lee, Hyun Young; Park, Jae Joon; Khandwala, Yash S.; Jeong, In Gab; Chung, Benjamin I.
Abstract: Objective: To investigate the overall prevalence of benign pathology after partial nephrectomy (PN) and identify predictive factors for benign pathology after PN. Methods: A systematic review was performed following the PRISMA guidelines. PubMed/Medline, Embase, and the Cochrane Library were searched up to January 2019PRISMA guidelines. The data for the meta-analysis and network meta-analysis were pooled using a random-effects model. Results: There were 144 studies included in the final analysis, which was comprised of 79 observational studies (n = 37, 300) and 65 comparative studies (n = 18, 552). The overall prevalence rate of benign pathology after PN was 0.19 (95% CI: 0.18–0.21). According to the procedure types, the prevalence rate of benign pathology was 0.17 (95% CI: 0.15–0.19), 0.24 (95% CI: 0.22–0.27), and 0.16 (95% CI: 0.15–0.18) in open partial nephrectomy, laparoscopic partial nephrectomy, and robot-assisted laparoscopic partial nephrectomy, respectively. The significant moderating factors were gender, publication year, the origin of the study, and procedure types. The three most common benign pathology types were oncocytomas, angiomyolipomas, and renal cysts (44.50%, 30.20%, and 10.99%, respectively). Conclusions: The overall prevalence of benign pathology after PN was not low and it was affected by female gender, studies published before 2010, studies originating from Western areas, and laparoscopic procedure types. Highlights: This is the first study to investigate the overall prevalence of benign pathology after partial nephrectomy (PN). The overall prevalence rate of benign pathology after PN was 0.19 (95% CI: 0.18–0.21). The other interesting result from our study was that procedural types of PN were a predictive factor for benign pathology after PN. In a comparison of minimally invasive (LPN and RAPN) and open procedures (OPN), minimally invasive procedures showed a higher prevalence of benign pathology after PN (0.198, 95% CI: 0.183, 0.214) compared to open procedures. One distinguishing feature of our study is that this study used the pooled data of proportion of being pathology among 3447 patients. The most common pathology type was oncocytoma (44.50%).